SISTEM PEMANTAUAN DAN PENORMALAN SUHU BERBASIS INTERNET OF THINGS - sayuna, Tio; Belutowe, Yohanes Suban (Jurnal Publikasi Manajemen Informatika, 2025)
Green houses are closed agricultural facilities that rely heavily on stable temperature and environmental conditions to support optimal plant growth. Temperatures above 30°C can cause plant stress and reduce productivity, especially in coastal areas such as Kupang City where temperatures vary from 22°C to 34.9°C. Therefore, a reliable and adaptive temperature regulation system is needed. This research aims to design and implement an Internet of Things (IoT)-based air temperature monitoring and normalization system using NodeMCU ESP32, DHT22 sensor, anemometer, and rain sensor. The system is able to read real-time temperature and wind speed conditions and activate the cooling fan automatically when the temperature exceeds a predetermined threshold. Environmental data is sent via Telegram, enabling efficient remote monitoring. The implementation results show that the system can work stably and responsively to temperature changes, thus supporting optimal and sustainable green house management.